2020
DOI: 10.5222/bmj.2020.02411
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in Patients With Early- Onset Rheumatoid Arthritis

Abstract: Objective: Rheumatoid arthritis (RA) is a chronic inflammatory and destructive joint disease that affects 0.5-1% of the world's population and commonly leads to significant disability and consequent impairment of quality of life. Osteoporosis is an early and common feature in RA and occurs during the course of the disease as extra-articular manifestation of rheumatoid arthritis, which may result in increased risk of fractures, morbidity, and mortality. The aim of this study was to evaluate changes in bone mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Some authors observed an increased bone mass at the lumbar spine, radius, and tibia in obese women, but not in men [53,54]. Other authors report a positive correlation between BMI and BMD also in the radial shaft and ultra-distal radius [55]. Quantitative imaging methods, such as HR-pQCT, demonstrated higher cortical BMD, higher trabecular BMD, and greater trabecular number at the distal radius and distal tibia in obese people, but no difference in bone size between obese and normal adults [34,56].…”
Section: Obesity and Mineral Bone Densitymentioning
confidence: 99%
“…Some authors observed an increased bone mass at the lumbar spine, radius, and tibia in obese women, but not in men [53,54]. Other authors report a positive correlation between BMI and BMD also in the radial shaft and ultra-distal radius [55]. Quantitative imaging methods, such as HR-pQCT, demonstrated higher cortical BMD, higher trabecular BMD, and greater trabecular number at the distal radius and distal tibia in obese people, but no difference in bone size between obese and normal adults [34,56].…”
Section: Obesity and Mineral Bone Densitymentioning
confidence: 99%
“…It is also worth noting that the Mental Health Center has made available the toll-free hotline 0800 88 881 in advising citizens on any mental health concerns during the pandemic [15]. in Kosovo there are 105,711 people infected with COVID-19.…”
mentioning
confidence: 99%
“…88 Према уџбенику, он је био "осмишљен да сакрије и оправда анексију албанских земаља" и представљао је "озбиљно кршење права албанског народа". 89 Не помиње се сарадња Есад-паше Топтанија са Србијом ни споразуми које је он закључио са српском владом, а који су предвиђали стварање царинске и реалне уније ове две државе. 90 У уџбенику се не помиње ни сарадња српске владе са Ахмед-бегом Зогуом, поглаваром Маћана из северне Албаније, преко кога је српска влада хтела да осигура да не дође до побуне у овом делу Албаније.…”
unclassified